(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article studies the effect of plant alkaloids 1-O-benzoylnapellin, zongorin, dihydroathysine and 6-benzoylheterathisine on the contractile activity of rat tracheal smooth muscle cells. It was found that 1-O-benzoylnapellin, dihydratizine, 6-benzoylheterazine and zongorin under conditions of КСl -induced contracture exhibit a relaxant effect, which may be due to their interaction with potential-dependent Са2+ channels of plasma membranes and suppression of the entry of Са2+ ions into the MMC of rat trachea.